Association of betaine with blood pressure in dialysis patients. Issue 2 (25th January 2018) - Wang, Lulu; Zhao, Mingming; Liu, Wenjin; Li, Xiurong; Chu, Hong; Bai, Youwei; Sun, Zhuxing; Gao, Chaoqing; Zheng, Lemin; Yang, Junwei
Abstract : Mechanisms underlying elevated blood pressure in dialysis patients are complex as a variety of non‐traditional factors are involved. We sought to explore the association of circulating betaine, a compound widely distributed in food, with blood pressure in dialysis patients. We used baseline data of an ongoing cohort study involving patients on hemodialysis. Plasma betaine was measured by high performance liquid chromatography in 327 subjects. Blood pressure level was determined by intradialytic ambulatory blood pressure monitoring. The mean age of the patients was 52.6 ± 11.9 years, and 58.4% were male. Average interdialytic ambulatory systolic and diastolic blood pressure were 138.4 ± 22.7 mm Hg and 84.4 ± 12.5 mm Hg, respectively. Mean plasma betaine level was 37.6 μmol/L. Multiple linear regression analysis revealed significant associations of betaine with both systolic blood pressure (β = −3.66, P = .003) and diastolic blood pressure (β = −2.00, P = .004). The associations persisted even after extensive adjustment for cardiovascular covariates. Subgroup analysis revealed that the association between betaine and blood pressure was mainly limited to female patients. Our data suggest that alteration of circulating betaine possibly contributes to blood pressure regulation in these patients.